Evaluasi Kualitas Layanan terhadap Operator Telekomunikasi: Tinjauan Perspektif Pelanggan - Rizka Shoumil Ilhami; Dino Rimantho (Jurnal Optimasi Sistem Industri, 2017)
PT. X organizes the office promotion every year, however it has not implemented the performance appraisal concept. This study was conducted on junior analyst at Laboratory Department of Routine Test in PT.X which has the highest number of employees in PT. X. This research aimed to find out the performance appraisal criteria and sub-criteria of the junior analysts, provide the weighting for each criteria and sub-criteria using Analytic Hierarchy Process (AHP) method, and recommend the planning framework of performance appraisal for junior analyst using Rating-Scale method in order to conduct the office promotion. The main criteria derived from this research were attendance, working target attainment, work thoroughness, proactive, empathy, cooperation (team/organization), analytical thinking, and flexibility. The result showed the working target attainment as the most important of the criterion approximately 0.248. Moreover, the consistency ratio around 0.020. In addition, the result of this research is applicable and could be proposed for conducting performance appraisal of junior analysts at Laboratory Department of PT. X in order to perform the office promotion.